Pelatihan Pembuatan Video Promosi Berbasis Smartphone Sebagai Upaya Peningkatan Literasi Digital Marketing Siswa SMA Carnegie Medan - Sjukun; Fenny Fenny; Yusuf Taufik (Jurnal Pemberdayaan Masyarakat, 2026)
The development of digital technology has transformed marketing activities from conventional methods into more interactive and technology-based digital marketing practices. However, the high level of internet usage among adolescents has not been fully accompanied by the ability to utilize technology productively. This community service activity aimed to improve students’ digital marketing literacy through smartphone-based promotional video training at Carnegie Senior High School Medan. The method used was a participatory and practical approach consisting of material presentation, demonstrations, hands-on practice, and evaluation. The participants were 40 students from grades XI and XII. The results showed an improvement in students’ understanding of digital marketing concepts and their ability to create simple promotional videos. Based on the evaluation results, approximately 85% of students understood the basic concepts of digital marketing and around 80% were able to create promotional videos with a fairly good structure. In addition, the activity encouraged a shift in students’ mindset regarding smartphone usage from consumptive purposes to more productive and creative activities. Practice-based training proved effective in improving students’ digital skills while providing practical and relevant learning experiences aligned with the needs of the digital era.